Effect of maternal bisphenol exposure on adverse pregnancy and neonatal outcomes: The Japan Environment and Children’s study - Sugiura-Ogasawara, Mayumi; Suwannarin, Neeranuch; Tamada, Hazuki; Ebara, Takeshi; Ito, Yuki; Nakayama, Shoji F.; Takagi, Mai; Saitoh, Shinji; Kamijima, Michihiro (Environment international, 2025)
[Display omitted] •The association between maternal BPA exposure and pregnancy outcomes was evaluated.•Overall, 4523 mother–infant pairs from the JECS cohort were included in this study.•Urinary BPA levels in Japanese pregnant women were low.•Daily BPA intake exceeded TDI in 86.6% of participants, with potential health risks.•BPA exposure was not associated with pregnancy outcomes in Japanese women. Maternal exposure to bisphenols, including bisphenol A (BPA), reportedly results in adverse pregnancy and offspring health outcomes. However, large birth cohort studies on the risk of BPA exposure during pregnancy remain limited. Here, we examined bisphenols’ effects on adverse pregnancy and neonatal outcomes using data from the Japan Environment and Children’s Study, a nationwide birth cohort study. We selected 4523 women with pregnancies resulting in singleton live births. First-trimester urine concentrations of bisphenols A, F, S, and AF were determined via high-performance liquid chromatography-tandem mass spectrometry. We analyzed the association between BPA exposure and preterm birth, hypertensive disorders of pregnancy, gestational diabetes mellitus, small- and large-for-gestational-age infants, low birth weight, offspring physical and chromosome abnormalities using Bayesian logistic regression analysis after applying the GSimp imputation method for concentrations within the minimum reporting limit. Bisphenol detection rates were generally low (0.0–11.9 % of samples), except for that of BPA (71.5 %), and BPA concentrations were lower than those reported in previous international studies. The estimated BPA daily intake for 86.6 % of the study participants exceeded the European Food Safety Authority’s tolerable daily intake (0.0002 µg/kg/day). However, BPA intake was not significantly associated with any outcome. These findings suggest that BPA’s current exposure levels do not affect measured pregnancy and neonate outcomes in Japan. Here, although BPA levels reflect only recent exposure, the potential health risks associated with BPA underscore the need for further research to investigate the long-term effects of low-level exposure on maternal and child health.